2022 16th International Workshop on Variable Structure Systems (VSS) 2022
DOI: 10.1109/vss57184.2022.9902105
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fractional-Order Sliding Mode Control Applied to an Energy Harvesting System

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…We can cite, for instance, the work [5], where authors reported that the use of a Fractional Order Proportional Integral Derivative (FOPID) controller produced a significantly smaller control signal than the classic Proportional Integral Derivative (PID) controller, which would save energy for the actuator. Also, in [6], authors reported a lower control energy used when a Fractional Order Sliding Model Control (FOSMC) was applied to an energy harvesting system, compared to the classic non-integer case. In [7], on the other hand, Model Reference Adaptive Control (MRAC) schemes were presented, using orders for the adaptive laws in the interval (0, 1], which were obtained through Particle Swarm Optimization.…”
Section: Introductionmentioning
confidence: 99%
“…We can cite, for instance, the work [5], where authors reported that the use of a Fractional Order Proportional Integral Derivative (FOPID) controller produced a significantly smaller control signal than the classic Proportional Integral Derivative (PID) controller, which would save energy for the actuator. Also, in [6], authors reported a lower control energy used when a Fractional Order Sliding Model Control (FOSMC) was applied to an energy harvesting system, compared to the classic non-integer case. In [7], on the other hand, Model Reference Adaptive Control (MRAC) schemes were presented, using orders for the adaptive laws in the interval (0, 1], which were obtained through Particle Swarm Optimization.…”
Section: Introductionmentioning
confidence: 99%